2020
DOI: 10.1155/2020/5659738
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Anti‐Inflammatory Effect of Dehydrocostus Lactone on DSS‐Induced Colitis in Mice

Abstract: Background. Dehydrocostus lactone (DL), one of the main active constituents in Aucklandia lappa Decne. (Muxiang), reported to have anti-inflammatory, antiulcer, and immunomodulatory properties. However, the effect of DL on ulcerative colitis (UC) has not been reported. To analyze the anti-inflammatory potential role of DL in UC, we provide a mechanism for the pharmacological action of DL. Methods. The experimental model of UC was induced by using oral administration of 2% dextran sulfate sodium (DSS) with drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…In the current study, there was a significant activation of IL‐6/STAT‐3 signaling and treatment with mesalazine significantly decreases IL‐6 and its downstream target STAT‐3 molecule level in colon tissues and these results are in agreement with [47,48]. Also, atorvastatin strongly downregulates IL‐6/STAT‐3 signaling and these results are in the same line of other reports [49,50].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, there was a significant activation of IL‐6/STAT‐3 signaling and treatment with mesalazine significantly decreases IL‐6 and its downstream target STAT‐3 molecule level in colon tissues and these results are in agreement with [47,48]. Also, atorvastatin strongly downregulates IL‐6/STAT‐3 signaling and these results are in the same line of other reports [49,50].…”
Section: Discussionsupporting
confidence: 93%
“…Zhou et al were the first to report the anti-inflammatory potential ofDEH to treat ulcerative colitis in mice. Accordingly, the protective mechanism of DEH may be involved in reducing inflammation and improving colorectal barrier function via downregulating the IL-6/STAT3 signaling [ 281 ]. The anti-inflammatory effect of COS has also recently attracted strong attention.…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…Dehydrocostus lactone is an active compound from Aucklandia lappa and inhibits lipopolysaccharide (LPS)-induced TNF-α production in RAW 264.7 cells and mice [ 26 ]. Moreover, it has recently been reported that the oral administration of dehydrocostus lactone ameliorates DSS-induced colitis via the reduction of the expression of proinflammatory cytokines, such as TNF-α, IL-1β, IL-6, and IL-17 [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%